Konseling Kelompok Inokulasi Stres untuk Mengurangi Kecemasan Akademik di Era Pandemi - Srianturi, Yanuari; Dyahpalupi, Elvia Purwaningrum (Universitas Mathla'ul Anwar Banten, 2023)
This study aims to test the effectiveness of group counseling with stress inoculation training techniques to reduce student school as research subjects who were selected using purposive sampling technique. The results showed that group counseling with the stress inoculation training technique was effective in reducing student anxiety in facing exams in the era of the covid-19 anxiety in facing exams in the era of the covid-19 pandemic. The design of this study used an experimental method with a pre-test – post test. Students' exam anxiety was measured by the Achievement Emotions Questionnaire (AEQ) Scale. The subject of this research involved 50 students of class XII junior high pandemic. The findings of this study prove the effectiveness of group counseling services with stress inoculation techniques to reduce students' academic anxiety in facing exams in the covid-19 pandemic era.